Buginese Communication Heritage in Educational Contexts: An Overview of Literacy Contributions within the Diaspora - Saleh, Nor Shela; Rosli, Mohd Shafie; Andi Sukri Syamsuri; Daeng Jaafar Saadon (Human Sustainability Procedia, 2025)
The preservation of Buginese heritage is crucial for the cultural landscape of the Buginese community. The Buginese language is a vital aspect of this heritage, but its use, especially among younger generations, is in decline. Consequently, this study was undertaken to explore the perspectives of previous researchers on the issues surrounding Buginese communication heritage. Two primary objectives were established: first, to investigate the views of past researchers regarding the factors contributing to the decline in the use of the Buginese language, and second, to assess their recommendations for raising awareness about the preservation of the Buginese language. The study also incorporates several relevant communication theories for practical application, including the Communication Theory of Identity (CTI), Relationship Theory, Intercultural Communication Theory, and Face Theory. Employing a critical analysis approach, the research utilizes a systematic review of existing literature. The findings reveal four primary factors that contribute to the decline of Buginese communication heritage: disruption of language identity, challenges in communication adaptation, difficulties with assimilation, and limitations in Buginese language education. To raise awareness of the Buginese language heritage, four key actions are proposed: presentations featuring songs and poems, utilising media platforms, producing Buginese films, and incorporating the Buginese language into educational institutions. It is hoped that these findings will enhance the sustainability of Buginese communication heritage and indirectly contribute to Sustainable Development Goal 11.4, which aims to protect the world’s cultural and natural heritage.